ENGLISH TEACHER’ STRATEGY IN TEACHING LISTENING SECTION OF TOEFL PREPARATIONS - Wahhab Abdul Khobir; Aa Qonaatun (Journal of English Language Teaching and Literature (JELTL), 2020)
This research was intended to describe the strategies used by the teacher in teaching TOEFL preparation to support the students especially listening skill, the steps the teacher to implementing the strategies teacher, and the problem faced in enhancement 25% listening score in listening skill. This methodology was qualitative research with case study, the subject of the research was English teacher TOEFL preparation in EF Course Cilegon. The collecting data of this research used data display, data reduction and conclusion focus this research is strategies in teaching listening section in TOEFL and sub focus are direct and indirect in teaching listening section in TOEFL Preparation. The result strategies of this research are used simulation, discussions, giving tips and tricks, the course used ICT modern era, games, and motivation, the conclusion is There are some statements for the student participant about teacher strategies in teaching TOEFL Preparation. They are: First, teacher strategies can improve confidence in good speaker and listener. Second, teacher strategies can make students feel easier to take exam TOEFL. Third, the student often listening native speakers to understand can be enhanced. Fourth, the student can be more active how take TOEFL be well. the last, the student knows how to know type question in TOEFL especially listening section of the strategies. The writer found sixth strategies used by the EF Cilegon to teach TOEFL Preparation especially listening section.